Boundary value problems for differential inclusions with fractional order - HAMANI, Samira; Benchohra, Mouffak (Discussiones Mathematicae, Differential Inclusions, Control and Optimization, 2008)
In this paper, we shall establish su cient conditions for the existence of solutions for a boundary value problem for fractional di erential inclusions. Both cases of convex valued and nonconvex valued right hand sides are considered.
Keywords: di erential inclusion, Caputo fractional derivative, fractional integral, existence, xed point. 2000 Mathematics Subject Classi cation: 26A33, 34A60.